System change evaluation: Insights from The Rippel Foundation and its ReThink Health initiative. Issue 170 (1st September 2021) - Gates, Emily F.; Fils‐Aime, Francisca
Abstract: This chapter explores evaluation about and for system change within a case study of The Rippel Foundation's ReThink Health initiative. Their work involves field building to understand and shift what constrains current systems influencing health and well‐being and place‐based efforts to change systems carried out with regionally focused stewards. Guiding questions addressed how ReThink Health envisions, supports, and evaluates system change. Data included document review and group and individual interviews with staff members followed by iterative cycles of descriptive pattern coding and analysis. Seven, interrelated findings depict system change as (1) reframing problems and (2) cultivating stewardship supported by (3) adapted and new tools. Additionally, evaluation (4) fuels learning, (5) uses a developmental theory of system change, (6) assesses changes to system conditions, and (7) seeks to continuously develop value. Authors identify considerations for others engaged in system change evaluation.